A study on perceived value as a parallel between quality and kitsch in the design assessment of industrial products - Craciun, Alexandra Elena (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
The present paper represents a study that examines the relationship between the concepts associated with kitsch and quality approached as antagonistic concepts, for which was considered the direct connection to the product and its defining characteristics described as the product features, colour, form, material and dimensioning. Considering the relative influence of the proposed features, it was generated a series of concepts that represent the basis of the analysis format, on which numerical values will be assigned. The research contributes to industrial product design assessment in the situation where the product is approached from the perspective of the intrinsic components of the perceived value, being proposed an analysis model that starts from the relative importance ratios of the product features considered in direct relation with a correspondent assigned value.